POST-CHEMOTHERAPY TREATMENT IN NATIONAL HEALTH INSURANCE BREAST CANCER PATIENTS AT YOGYAKARTA CITY HOSPITAL - Anggraeni, Dita Putri; Yuliastuti, Fitriana (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Breast cancer accounts for approximately 16.6% of 396,914 cases of cancer and is one of the most fatal and common diseases among women. Treatment of breast cancer mostly has side effects, but the incidence of drug side effects does not always appear because the target drug does not selectively act on the target action. The aim of this study was to find a picture of post-chemotherapy treatment in breast cancer chemotherapy patients participating in the National Health Insurance at RSUD Yogyakarta. Observational method: Retrospective collection of data obtained from patients’ medical records. The subjects included patients with breast cancer at RSUD Yogyakarta who met the inclusion criteria for the primary diagnosis of breast cancer and received chemotherapy medication during the period of 2020. The univariate analysis showed the distribution of frequency and percentage of respondent characteristics, including age, gender, number of patients, single and combination chemotherapy drugs, generic and commercial drugs, and single or combination post-chemotherapy medications. The results were obtained from 72 patients who underwent 4 periods of chemotherapy. The most frequently used chemotherapy regimens for each period were the period 1 combination of Brexel, Epirubicin, Carboplatin. Period 2 combination of the Brexel and Zometa regimes. Periode 3 combination brexel, epirubicine, and carboplatin. The most widely used combination of post-chemotherapy drugs in periods 1-4 was the combination of Ranitidine and Ondansetron. Keywords: Ca Mamae, Chemotherapy, Regimen, Drugs